2017
DOI: 10.1111/jcmm.13416
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone regulates the expression and functional activity of sphingosine‐1‐phosphate receptors in the rat corpus cavernosum

Abstract: The bioactive lipid sphingosine‐1‐phosphate (S1P) regulates smooth muscle (SM) contractility predominantly via three G protein‐coupled receptors. The S1P1 receptor is associated with nitric oxide (NO)‐mediated SM relaxation, while S1P2 & S1P3 receptors are linked to SM contraction via activation of the Rho‐kinase pathway. This study is to determine testosterone (T) modulating the expression and functional activity of S1P receptors in corpus cavernosum (CC). Adult male Sprague‐Dawley rats were randomly divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
(87 reference statements)
0
9
0
Order By: Relevance
“…Studies have demonstrated that S1PR2 and S1PR3 are the major types of S1PRs to transduce cellular effects of S1P in most of mammalian cell types ( 19 , 31 , 32 , 33 ). To examine whether S1PR2 and S1PR3 mediate S1P-induced activation of the STAT3/miR-135b/β-TrCP/YAP/Notch3 signal pathway and PASMCs proliferation, cells were previously treated with JTE013 (a selective S1PR2 antagonist, 10-μM) or CAY10444 (a selective S1PR3 antagonist, 10-μM) for 1 h and then stimulated with S1P, the phosphorylation level and total protein level of STAT3 and protein levels of β-TrCP, YAP, Notch3, and NICD3 were examined using Western blotting, the level of miRNA-135b was detected using qRT-PCR, and proliferation of cells was evaluated by the EdU incorporation assay.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have demonstrated that S1PR2 and S1PR3 are the major types of S1PRs to transduce cellular effects of S1P in most of mammalian cell types ( 19 , 31 , 32 , 33 ). To examine whether S1PR2 and S1PR3 mediate S1P-induced activation of the STAT3/miR-135b/β-TrCP/YAP/Notch3 signal pathway and PASMCs proliferation, cells were previously treated with JTE013 (a selective S1PR2 antagonist, 10-μM) or CAY10444 (a selective S1PR3 antagonist, 10-μM) for 1 h and then stimulated with S1P, the phosphorylation level and total protein level of STAT3 and protein levels of β-TrCP, YAP, Notch3, and NICD3 were examined using Western blotting, the level of miRNA-135b was detected using qRT-PCR, and proliferation of cells was evaluated by the EdU incorporation assay.…”
Section: Resultsmentioning
confidence: 99%
“…S1P regulates cellular activities via five types of S1PRs in mammalian cells, and S1PR2 and S1PR3 are the major types to transduce cellular effects of S1P in most of cell types ( 19 , 31 , 32 , 33 ). Chen et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study demonstrated vascular endothelial cells expressed specific S1P1 receptors, which were important for regulating vascular tone in blood vessels, and that activation of S1P1 receptor promoted vascular relaxation via the eNOS pathway (Michel, Mulders, Jongsma, Alewijnse, & Peters, ). Moreover, Yin et al () reported testosterone activated S1P1 in the CC of castrated rats. S1P1 receptor was reported to activate the Akt pathway (Rosen, Gonzalez‐Cabrera, Sanna, & Brown, ), which was found to promote neuronal survival and anti‐apoptotic effects in many cell types (Hasegawa, Suzuki, Sozen, Rolland, & Zhang, ; Hemmati et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…Safarian, Khallaghi, Ahmadiani, and Dargahi () reported activation of Sphingosine‐1‐phosphate (S1P) receptor‐regulated protein kinase B (Akt)/Forkhead box (FOXO) 3a pathway to enhance cell survival in response to oxidative stress. Moreover, Yin et al () suggested testosterone could enhance the activity of S1P receptor 1 (S1P1) in castrated rats. Similarly, S1P receptor‐mediated activation of Akt pathway protected granulosa cells against oxidative stress (Nakahara et al, ).…”
Section: Introductionmentioning
confidence: 99%